Analisis Komparatif Laporan Keuangan Guna Mengukur Kinerja Keuangan Pada PT. Jasamarga Tbk. - Mutiah, Yumna; Hasibuan, Nur Fadhilah Ahmad (Maisyatuna, 2024)
PT. Jasamarga Tbk. As a company operating in the infrastructure sector, it is involved in various projects and investments that require careful financial performance evaluation. The COVID-19 pandemic has had various impacts on the financial performance of companies including PT. Jasamarga Tbk. This research aims to find out how the financial performance of PT. Jasamarga Tbk during 2018-2022. The data analysis technique in this research uses financial ratios and focuses on calculating profitability as measured from several aspects, namely Gross Profit Margin (GPM), Net Profit Margin (NPM), Return On Assets (ROA), and Return On Equity (ROE). This research uses a qualitative descriptive method with comparative analysis. The subjects in this research were PT. Jasamarga Tbk and the object of this research is the financial report of the company PT. Jasamarga during 2018-2022. The type of data used is secondary data, namely data collected by other parties or other sources accessed from the company's official website. The data collection technique used is a documentation technique, namely by collecting data from the company's financial reports which have been officially published in the form of an Annual Report issued by the official website of PT. Jasamarga. The research results show that the average value of the profitability ratio in 2018 experienced quite good growth, namely 8.51%, then in 2019 it experienced an increase which was considered good, namely 10.84%. In 2020 there was a decline of 9.64% which is considered quite good. In 2021 the average profitability ratio experienced an increase which was considered good, namely 13.17% and in 2022 experienced a significant increase, namely 17.59% which was considered very good. Overall, the average profitability ratio value of PT. Jasamarga's 11.95% is in the interpretation of 10% - <15%, which means the financial performance of PT. Jasamarga Tbk. in 2018-2022 is in a good assessment.